Sediment delivery ratio in a small semi-arid watershed under conditions of low connectivity - Santos, Julio Cesar; de Andrade, Eunice; Medeiros, Pedro Henrique; Palácio, Helba; de Araújo Neto, José (Revista Ciência Agronômica, 2016)
The semi-arid region in the northeast of Brazil is characterised by rains of high intensity and short duration, with the processes of erosion being aggravated by an inappropriate land-use model. In this region, the lack of measured data for runoff and sediment yield increases the need to apply hydro-sedimentological models in estimating erosion, requiring knowledge of the actual sediment delivery ratio for the region. The aim of this study therefore, was to map soil erosion, making use of the Universal Soil Loss Equation (USLE), in the Iguatu Experimental Watershed (IEW). The mean annual sediment delivery ratio (SDR), and the SDR for individual events, was calculated from hydro-sedimentological measurements, contributing to an understanding of the processes of sediment propagation in the Brazilian semi-arid region, allowing identification of areas susceptible to water erosion. The IEW has an area of 16.74 km2 and is equipped with sensors for the continuous measurement of rainfall, flow and sediment yield. The mean annual SDR for the IEW was 0.37%. The SDR for individual rainfall events ranged from 0.08 to 1.67%, with an average of 0.68%. Among the main variables that influence the SDR for individual events is the magnitude of rainfall depth and antecedent soil moisture that can be better represented by the total antecedent precipitation of the previous 15 days. According to maps of soil loss, only 6.27% of the watershed presented losses beyond tolerable limits.